Rhetorical Tropes of Nationhood in Nigeria's Presidential Campaign Speeches - Ahmed, Yunana; Agbonica Bello Eje , Monday; Z. Sabe, Charles (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
This paper examines the rhetorical tropes of nationhood in the 2015 presidential campaign speeches of Goodluck Jonathan. Drawing from Wodak et al. (2009) discourse-historical approach, Aristotelian classical rhetoric, and Mignolo (1995) decolonial approach, the paper provides insights into how Goodluck Jonathan uses the affordances of metonymy, metaphor and personification to articulate his version of national consciousness. The findings show that through the metonymic use of personal names such as Mustapha, and Christopher, Ade and Ada, Timi and Bunmi, Nnamdi and Namadi mostly from the three major ethnic groups (Hausa, Igbo and Yoruba), and the use of a number of personifications, such as “womb,” “thirsts,” and “destined,” positioning these words with Nigeria, Jonathan attempted to construct unification, unity, sameness and oneness in the midst of crises and diversity. Unfortunately, these ideas of unity follows the colonial government strategy of divide and rule where there is a preference to have a clear-cut division that coincided with three ethnic groups for easy administration. Thus, the depiction of Nigeria as comprising just three ethnic groups through the metonymic use of names has become an incentive for political competition and group formation in national politics.